Facilitators and barriers for implementation of a UK standardized core curriculum for medical schools, a dermatology perspective - Sharma, Maulina (2023)
There is no standard medical curriculum across UK medical schools. The General Medical Council (GMC) provides generic learning outcomes for medical schools.Specialty curriculum implementation in medical schools is varied and inconsistent. This PhD thesis aimed to explore the facilitators and barriers for implementation of a nationally recommended specialty core-curriculum for UK medical schools, using Dermatology as a specialty perspective.